Sustainable and smart logistics centers: Challenges and opportunities for Ukraine's transport system - Yuriy Vovk; Iryna Vovk; Uliana Plekan; Oleg Tson; Vasyl Oleskyuk (Journal of Sustainable Development of Transport and Logistics)
Purpose: The devastation of Ukraine's transport infrastructure during the ongoing conflict has created immense challenges and a unique opportunity to rethink and rebuild the nation's logistics system for the twenty-first century. This paper investigates how integrating sustainable and smart logistics centers can catalyze Ukraine's economic recovery and future competitiveness. Methodology: Drawing on a mixed-methods approach, including satellite-based damage assessments, comparative analysis with leading European logistics models, and in-depth case studies of Ukrainian logistics hubs, the study explores both the obstacles and the transformative potential of digitalization, automation, and green technologies in the Ukrainian context. Results: The findings reveal that while Ukraine faces severe barriers, such as regulatory fragmentation, underinvestment in digitalization, and a legacy of war-related destruction, there are clear pathways forward. International best practices, particularly those from Germany, France, and Poland, demonstrate that multimodal, technology-driven logistics centers can accelerate recovery and foster sustainable growth. Case studies from Lviv and Odesa show that even amid a crisis, adopting solar energy and automated systems leads to measurable efficiency gains and cost reductions. The research also highlights the critical importance of harmonizing Ukrainian regulations with European Union standards, leveraging EU funding for corridor modernization, and fostering public-private partnerships to drive innovation. Theoretical Contribution: Theoretically, the paper advances the understanding of logistics center development in transition economies, proposing a framework synthesizing digital, environmental, and organizational innovations. Practical Implications: It offers policymakers and industry leaders actionable recommendations for regulatory reform, investment prioritization, and technology adoption to position Ukraine as a future leader in sustainable, smart logistics within the European transport network.